2022
DOI: 10.3390/nano12193340
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Strain Study of Cuprate Superconductors

Abstract: Cuprate superconductors have attracted extensive attention due to their broad promising application prospects. Among the factors affecting superconductivity, the effect of strain cannot be ignored, which can significantly enhance or degrade superconductivity. In this review, we discuss and summarize the methods of applying strain to cuprate superconductors, strain measurement techniques, and the influence of strain on superconductivity. Among them, we pay special attention to the study of strain in high–temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 114 publications
0
8
0
Order By: Relevance
“…This would make it very difficult to compute the vibrational properties in the bulk, and the majority of the properties on the slab case due to the excessive computational time required. It is important to note that the results obtained here represent the effect of strain in samples close to optimal doping, and not in under-doped samples, where strain effects appear to be greater [25]. It would be interesting for a theoretical work to cover this problem in the future.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…This would make it very difficult to compute the vibrational properties in the bulk, and the majority of the properties on the slab case due to the excessive computational time required. It is important to note that the results obtained here represent the effect of strain in samples close to optimal doping, and not in under-doped samples, where strain effects appear to be greater [25]. It would be interesting for a theoretical work to cover this problem in the future.…”
Section: Introductionmentioning
confidence: 89%
“…One possible way to achieve this is by generating strain in thin films. This strain can be induced by the mismatch with the single crystal substrate (epitaxial), or by the presence of grain boundaries, stacking faults, intergrowth, defects (residual), among others [15][16][17][18][19][20][21][22][23][24][25]. More recently, YBa 2 Cu 3 O 7 (YBCO) has been deposited on piezoelectric substrates, managing to control the range and value of the strain by applying an electric field after the sample has been grown, obtaining reversible effects on the critical temperature and a linear dependence with the in-plane strain [26,27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The property led scientists to search for forms of high-temperature superconductors with stronger current-carrying capacity by articially designing the shape, density and distribution of pinning centers. [24][25][26][27] Related studies have shown that the nanoscale second phase has superior properties J c values as a pinning center for superconductors. In contrast, the effect of doping of Er and Y elements on Bi2212 has rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%